Employees Voice and Silence on Leadership and Organizational Culture as Mediation Variables - Raffila Irawan, Raja; Rahmat, Adi; Wardi, Jeni (SAINS ORGANISASI, 2023)
This research study delves into the dynamics of employee behavior in relation to leadership and organizational culture, focusing on the roles of voice and silence as mediating variables. The study aims to understand how employees' perceptions of leadership and the prevailing organizational culture influence their decisions to speak up (voice) or withhold their opinions (silence). By investigating the mediating effects of voice and silence, the study seeks to provide insights into the intricate interplay between leadership effectiveness, organizational culture, and employee communication behavior. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to capture a comprehensive view of the subject matter. Through a survey administered to a diverse sample of employees across various industries, data will be collected regarding their perceptions of leadership styles, organizational culture dimensions, and their tendencies to engage in vocal behaviors or remain silent. Concurrently, qualitative interviews with selected participants will delve deeper into the underlying motivations, barriers, and contextual nuances shaping employees' decisions to voice their opinions or remain silent. The study hypothesizes that both leadership styles and organizational culture significantly impact employees' likelihood to engage in voice or silence behaviors. Furthermore, it posits that employees' perceptions of leadership and organizational culture act as mediating factors in this relationship. By employing advanced statistical analyses and thematic coding techniques, the study aims to validate these hypotheses and uncover potential mechanisms through which leadership and culture jointly influence employee communication behavior. The findings of this research are expected to contribute to the existing body of knowledge by shedding light on the complex relationship between leadership, organizational culture, and employee communication behaviors. The study's outcomes could offer practical implications for organizational leaders and managers, helping them comprehend the importance of fostering an inclusive culture that encourages employee voice and reduces the prevalence of silence. Ultimately, the research strives to enrich the understanding of the dynamics that shape employee engagement, communication, and participation within their respective organizations.